2004
DOI: 10.1167/iovs.03-0016
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Membrane as a Carrier for Cultivated Human Corneal Endothelial Cell Transplantation

Abstract: The cell density and morphology of cHCECs on AM were similar to those of normal corneas, and cHCECs on AM were functional in vivo. These results indicate that AM maintains HCEC morphology and function and could serve as a carrier for cHCEC transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
227
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(237 citation statements)
references
References 19 publications
4
227
0
6
Order By: Relevance
“…TE-HCE transplants should provide an effective treatment for PCEP. This finding is in accordance with previous reports (Ishino et al, 2004;Fan et al, 2009b;2010b). The eye pressures of TE-HCE, PKP, and control eyes fluctuated from time to time.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…TE-HCE transplants should provide an effective treatment for PCEP. This finding is in accordance with previous reports (Ishino et al, 2004;Fan et al, 2009b;2010b). The eye pressures of TE-HCE, PKP, and control eyes fluctuated from time to time.…”
Section: Discussionsupporting
confidence: 94%
“…TE-HCE transplants were capable of recovering the corneal transparency of PCEP rabbits, maintaining the transparency of corneas for longer than previously reported (Aboalchamat et al, 1999;Ishino et al, 2004;Fu et al, 2006;Koizumi et al, 2008;Fan et al, 2009b;2010b;Proulx et al, 2009). The corneas of TE-HCE eyes became thinner and thinner with the time, while the corneas of PCEP and PKP eyes remained almost unchanged in thickness.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…It has also been demonstrated that denuded AM can be utilized as a feeder layer for some stem cells and may be used for neuronal differentiation (Miyamoto et al, 2004;Ueno et al, 2006;Meng et al, 2007). Denuded AM has been investigated as a carrier of chondrocytes, and it has been suggested that the AM can serve as a carrier matrix for cartilage regeneration (Jin et al, 2007). When epithelial and mesenchymal cells are seeded on a cellular scaffold created from the AM, the cells were highly interconnected and capable of penetrating the porous structure of the amnion scaffold.…”
Section: The Amniotic Membrane As a Scaffold For Tementioning
confidence: 99%
“…Materials like collagen, amniotic membrane, and biodegradable polymers have successfully been used in culture media and animal models. [80][81][82] Porcine corneal matrix and Descemet's membrane have also been used as scaffolds for transplanted cells allowing good transparency in cat and rat corneas, and maintaining cell properties after the transplant. 60,83 Human decellularized stromas have been used to culture HCECs, allowing them to retain the expression of Na þ /K þ -ATPase and ZO-1 markers for greater than 14 days.…”
Section: Cell Therapymentioning
confidence: 99%